2012
DOI: 10.1039/c2cc33407k
|View full text |Cite
|
Sign up to set email alerts
|

Dibenz[a,c]anthracene derivatives exhibiting columnar mesophases over broad temperature ranges

Abstract: We report the synthesis and characterization of a series of novel hexaalkoxydibenz[a,c]anthracenes. While the parent compound is not mesomorphic, the introduction of substituents in the 10- and 13-positions yields compounds with columnar liquid crystalline phases over very broad temperature ranges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…19 We also demonstrated that electrophilic bromination introduced substituents in the 10-and 13-positions. By careful control of the stoichiometry of bromine added, either the monobromo-derivative 6 or the dibromo-derivative 4 could be formed.…”
Section: Synthesismentioning
confidence: 92%
See 4 more Smart Citations
“…19 We also demonstrated that electrophilic bromination introduced substituents in the 10-and 13-positions. By careful control of the stoichiometry of bromine added, either the monobromo-derivative 6 or the dibromo-derivative 4 could be formed.…”
Section: Synthesismentioning
confidence: 92%
“…Variable-temperature powder X-ray diffraction studies on a representative compound in this series supports the phase assignment as a columnar hexagonal mesophase. 19 It is noteworthy that most of the compounds in series 4 do not crystallize D r a f t on cooling from the columnar mesophase but instead form glasses that preserve the order of the columnar mesophase. In some cases these glass transitions could be distinguished by DSC, while in other cases they were determined by polarized optical microscopy as the point at which the textures no longer changes upon shearing or compression.…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations